Mercury in Eisenia fetida and soil in the vicinity of a natural gas treatment plant in northern Croatia. Issue 2 (28th January 2016) - Crnić, Andreja Prevendar; Zgorelec, Željka; Šuran, Jelena; Jurasović, Jasna; Špirić, Zdravko; Levak, Stefani; Bašić, Ferdo; Kisić, Ivica; Srebočan, Emil
ABSTRACT: In the last two decades (1990–2012), as part of a mercury monitoring programme, earthworms and soils have been collected from four locations in the vicinity of a natural gas production and treatment plant near the village of Molve, Croatia. The aim of this study was to determine the concentration of mercury in the collected samples, monitor its changes over a longer period of time and determine the bioaccumulation of total mercury in earthworms ( Eisenia fetida ) from the soil. Total mercury concentrations in earthworms from the surroundings of four boreholes (Molve 9–12) ranged within 0.195–1.050, 0.129–1.0, 0.229–1.236 and 0.223–0.799 μg g −1 dry weight, while total mercury concentrations in different soil types at the same locations within 0.055–0.350, 0.035–0.250, 0.031–0.240 and 0.071–0.475 μg Hg g −1 of soil. The calculated mercury bioaccumulation factor ranged between 0.9 and 17.5. Mercury levels in soil and earthworms, as a tool for soil pollution assessment, suggested low mercury exposure and risks for human health in the monitored area.